(untitled) (Scriptura, 2015)
The relationship between media and children has been an intriguing issue in media studies. When media technology develops, problems regarding children’s lives raise. Particularly, this research study depicted the relation of media and character education, which became a focus in Indonesia’s education system. The researcher used quantitative approach to find, analyze, and present data to picture the connection of media and character education. This research study has been done by conducting a survey to students in Pelangi Kristus, a school that has been known as one of those which implement character education in its curriculum. The research study showed that there was no influence between frequency, duration, and intensity of using Facebook and character education in Pelangi Kristus school, both in negative and positive aspect. Even though there was internet access availability and variety of gadgets students owned, they were not beneficial for the students, except for entertaining themselves such as playing game. Thus, there should be a media literacy to help students understand the maximum benefit of using Facebook in Pelangi Kristus.